The Influence Of Fashion Orientation On The Choice Of Fast Fashion And Sustainability Fashion On The Buying Intention Of Indonesian Consumers - Awdyfakhri, Elgin; Ridanasti, Erlita (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
The emergence of fast fashion in the global fashion industry has changed consumer consumption patterns. However, unsustainable fast fashion consumption patterns pose a risk to environmental and social sustainability. Indonesia, the fourth most populous country in the world, has many consumers who use fashion products, including fast fashion. However, the fashion orientation factors and intentions that consumers have always lead to certain behaviors. This study aims to examine the factors that influence Indonesian consumer's behavior toward their choice of fashion products. Four hypotheses based on the theory of the influence of Fashion Oriented on the choice of Fast Fashion and Sustainability Fashion on Buying Intention of Indonesian consumers. Research was made to form a hypothesis system, as many as 150 valid questionnaires were collected by random sampling in several cities in Indonesia. Data analysis and hypothesis testing were conducted using SEM Amos statistical software. The results show that Indonesian consumer's behavior towards fashion products tends to be positively influenced by fast fashion. In contrast, fashion orientation has a negative impact on sustainability fashion. On the other hand, fast fashion and sustainability fashion have a positive influence on purchase intention. The findings provide insights into the habits and knowledge of Indonesian consumers in choosing fashion products.